Philosophy, History and Religious Polemicism in Abraham Ibn Daud - Fernández López, José Antonio (Scripta Mediaevalia, 2023)
Written almost simultaneously (c. 1160) by Abraham Ibn Daud, The Book of Tradition and The Exalted Faith respond to a common purpose, developed, respectively, from a historiographic and philosophical perspective: to define and defend rabbinic Judaism in the Iberian Peninsula, within the general framework of an apologia pro religione Judaica. Our objective in this present paper is to investigate the fundamental features of these two works from the perspective of the religious polemicism, showing the differences between the philosophical and historical version that each of them, respectively, represents.